2019
DOI: 10.3390/app9112351
|View full text |Cite
|
Sign up to set email alerts
|

Graphene-Coated Elliptical Nanowires for Low Loss Subwavelength Terahertz Transmission

Abstract: Graphene has been recently proposed as a promising alternative to support surface plasmons with its superior performances in terahertz and mid-infrared range. Here, we propose a graphene-coated elliptical nanowire (GCENW) structure for subwavelength terahertz waveguiding. The mode properties and their dependence on frequency, nanowire size, permittivity and chemical potential of graphene are studied in detail by using a finite element method, they are also compared with the graphene-coated circular nanowires (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…Later, Huang and Cong et al [34,53] proposed the GCNWs with a drop-shaped cross-section for guiding THz plasmons, and an extremely long propagation length (1 mm) with a very small focal spot with full width at half maximum (FWHM) about 10 nm could be achieved, which resulted from the distinctive mode field distribution caused by both the top and bottom arcs of the waveguide. In 2019, Teng et al [54] showed that graphene-coated elliptical nanowires (see Figure 4b) could be used for THz waveguiding, and a propagation length over 200 µm as well as a normalized mode area of approximately 10 −4~1 0 −3 could be obtained at 3 THz. Increasing long-short axis ratio could simultaneously achieve both long propagation length and very small FWHM of the focal spots.…”
Section: Gcnwsmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, Huang and Cong et al [34,53] proposed the GCNWs with a drop-shaped cross-section for guiding THz plasmons, and an extremely long propagation length (1 mm) with a very small focal spot with full width at half maximum (FWHM) about 10 nm could be achieved, which resulted from the distinctive mode field distribution caused by both the top and bottom arcs of the waveguide. In 2019, Teng et al [54] showed that graphene-coated elliptical nanowires (see Figure 4b) could be used for THz waveguiding, and a propagation length over 200 µm as well as a normalized mode area of approximately 10 −4~1 0 −3 could be obtained at 3 THz. Increasing long-short axis ratio could simultaneously achieve both long propagation length and very small FWHM of the focal spots.…”
Section: Gcnwsmentioning
confidence: 99%
“…Copyright Optical Society of America, 2014. (b) Graphene-coated elliptical nanowire and normalized electric field distribution[54].…”
mentioning
confidence: 99%
“…Based on the propagating properties of Surface Plasmon Polaritons (SPPs) on graphene, various plasmonic components have been designed and investigated in the THz frequencies such as sensors [5,6], couplers [7][8][9], filters [10][11][12], resonators [13][14][15], and circulators [16][17][18][19]. Among these devices, graphene-based waveguides play a remarkable role in graphene plasmonics, which are divided into various platforms such as planar [20][21][22][23][24][25][26][27][28], cylindrical [29][30][31][32][33], and elliptical structures [34][35][36][37]. It should be noted that graphene plasmonics is mostly used in the mid-infrared region whereas metal-based plasmonics is a promising candidate in near-infrared frequencies for various applications [38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…In the THz band, Huang et al [ 49 ] proposed a graphene-coated nanowire with a drop-shaped cross section to realize low loss waveguiding with an ultra-strong mode confinement. Additionally, a graphene-coated elliptical nanowire was suggested for ultra-deep subwavelength THz waveguiding [ 50 ]. Zhou et al [ 51 ] proposed a graphene-based hybrid plasmonic waveguide to achieve ultra-deep subwavelength modal field confinement.…”
Section: Introductionmentioning
confidence: 99%